2015
DOI: 10.1007/s10142-015-0460-1
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation regulates the abundance of osa-miR393a in contrasting rice genotypes under salinity stress

Abstract: MicroRNAs (miRNAs) are important molecules that regulate gene expression under salinity stress. Despite their evolutionary conservation, these regulatory elements have been shown to behave differently in different plant species under a particular environmental stress. In this study, we investigated the behavior of salt responsive osa-miR393a and its target gene (TIR1, LOC_Os05g05800) in salt-tolerant (FL478) and salt-sensitive (IR29) rice genotypes. It was found that the mature and precursor sequences of osa-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The similarly regulated miRNAs profiles and degrees may represent the fundamental mechanism of adapting to salt shock, and the difference might explain the distinct salt sensitivities [18]. Ganie et al [55] reported significantly different expression patterns of osa-miR393a and its targets between two different rice genotypes. The expression of osa-mi393a in salinity-sensitive genotype tremendously increased from 0 to 24 h under salinity stress, while the target steeply decreased relative to the tolerant genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarly regulated miRNAs profiles and degrees may represent the fundamental mechanism of adapting to salt shock, and the difference might explain the distinct salt sensitivities [18]. Ganie et al [55] reported significantly different expression patterns of osa-miR393a and its targets between two different rice genotypes. The expression of osa-mi393a in salinity-sensitive genotype tremendously increased from 0 to 24 h under salinity stress, while the target steeply decreased relative to the tolerant genotype.…”
Section: Discussionmentioning
confidence: 99%
“…The osa-miR393a has been reported to negatively regulate the salinity stress tolerance in rice by repressing the auxin signaling pathway and other mechanisms [49]. Usually, stress induces miRNAs to downregulate their target mRNA [45], and the reciprocal relationship between the expression of osa-miR393a and TIR1 exists at different time points during salt stress [17,55]. In our result, the target of miR393a was a TIR1-like protein which played an important role in abiotic stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The FL478, a salinity tolerant rice cultivar [ 3 ], was used for the gene expression study through qRT-PCR. Seeds were surface sterilized with sodium hypochlorite (3%) and were germinated on the germination papers.…”
Section: Methodsmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis and qRT-PCR analysis were performed according to the protocol described by Ganie et al [ 3 ]. For qRT-PCR study, 3 biological replicates per sample were used with 3 technical replicates for each biological replicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation